Value of Gallium-67 Scanning in Monitoring Therapeutic Effectiveness in a Patient with Relapsing Polychondritis - Ming-Che Chang; Shih-Chuan Tsai; Wan-Yu Lin (Kaohsiung Journal of Medical Sciences, 2008)
We present a 57-year-old man who had low-grade fever and painful, swollen and erythematous ears. Gallium-67 citrate scintigraphy (gallium scan) performed prior to the commencement of treatment showed increased gallium uptake in bilateral external ears, neck, mediastinum and bilateral pulmonary hili. The results of ultrasonography of both ears were compatible with the diagnosis of chondritis. The patient's clinical condition and laboratory data improved after a course of nonsteroidal anti-inflammatory drugs and steroids. Gallium scan performed after treatment showed a diminished uptake in the external ears, neck, and mediastinum. Gallium scintigraphy is a valuable tool for evaluating inflammatory activity and monitoring therapeutic response in patients with relapsing polychondritis.